The effect of insulated food container design on fish quality and transport costs - Rúnar Ingi Tryggvason 1994- (2019)
The main goal of the thesis was to evaluate the quality differences of Atlantic cod (Gadus morhua) and Atlantic salmon (Salmo salar) that had been stored and transported in different sized packaging solutions. The estimated costs of transporting fresh fish in different sized packaging was also evaluated. Drip loss, texture, processing yield, cooking yield, NMR and sensory methods were used as quality parameters. Different sized packaging solutions and pre-chilling methods had generally minor effects on the quality parameters evaluated in the present study, with the exception of drip loss. Drip loss was affected by packaging depth, chilling methods and storage duration. The greatest drip loss was detected in the largest packaging solutions and superchilling salmon also resulted in greater drip loss compared to iced salmon. New twin containers developed by Sæplast Iceland Ltd. can improve volume utilization during back freight by 53% compared to the most commonly used insulated containers in Iceland. The use of twin containers to export whole Atlantic cod and Atlantic salmon by sea to Europe can also reduce transportation costs significantly compared to common packaging solutions. The present results indicate that fresh fish container depth should be limited to 20-30 cm with regard to drip loss. Superchilling of fresh foods can have many benefits for producers and consumers but a controlled and optimized superchilling process is needed to ensure its effectiveness as compared to traditional icing. Sæplast Iceland Ltd. The Icelandic Student Innovation fund (project no. 185693-0091) AVS R&D Fund of Ministry of Fisheries and Aquaculture in Iceland (project no. R 016-17) Technology Development Fund (project no. 164698-061)